KUALITAS PELAYANAN DAN LOYALITAS KONSUMEN (Universitas Riau, 2016)
Service Quality and Customer Loyalty. This study aims to determine the effect of service quality on customer loyalty in PT. Nav Jaya Mandiri Home Singing Family Pekanbaru. The data used are primary data and secondary data. The analysis used is descriptive analysis and simple linear regression analysis using SPSS version 17. Samples were taken using accidental sampling method with a sample size of 100 respondents. Results of research conducted by a simple linear regression analysis obtained value b (regression coefficient) of 0.810 to 0.666 of Constanta where an independent variable that any change in the quality of service will affect the dependent variable namely customer loyalty. Based on these results it can be concluded that the value of the correlation coefficient has a high value or positive, it means that there is the influence of service quality on customer loyalty. While the value of determination between service quality and customer loyalty is 55.4% and the remaining 44.6% is determined by other factors.